INDIVIDUAL AND CREATIVE DEVELOPMENT OF THE FUTURE TEACHERS - THE WAY TO PREPARE HIGHLY QUALIFIED SPECIALISTS - Sherbyna, S.M.; Sherbyna, I.Yu. (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to individual creative development of future teachers in conditions of professional teaching.